Analysis of intraocular lens decentration and tilt after femtosecond laser-assisted cataract surgery using swept-source anterior optical coherence tomography - Yunhan Lee; Hoon Il Choi; Seonha Bae; Ho Seok Chung; Jae Yong Kim; Hun Lee (Heliyon, 2024)
Objective: To evaluate and compare the magnitude of intraocular lens (IOL) decentration and tilt following conventional and femtosecond laser-assisted cataract surgery (FLACS) using swept-source anterior optical coherence tomography (SS-OCT). Methods: In this retrospective observational study, we enrolled patients who underwent conventional cataract surgery or FLACS with the implantation of hydrophobic 1-piece monofocal IOL. The magnitude of IOL decentration and tilt were measured using SS-OCT. Visual acuity, intraocular pressure, spherical equivalent, axial length, contrast sensitivity, and satisfaction questionnaire were evaluated before and one-month post-surgery. Additionally, postoperative internal cylinder measurements were obtained using a wavefront aberrometer. Correlation factors between each parameter and IOL decentration or tilt were analyzed. Results: This study included 100 eyes from 100 patients. Mean IOL decentration and tilt were 0.21 ± 0.13 mm and 5.01 ± 1.49°, respectively. Conventional cataract surgery (versus FLACS, P = 0.001) and male sex (versus female, P = 0.047) were significantly correlated with higher postoperative decentration. Preoperative lens diameter (P < 0.001), preoperative lens tilt (P = 0.007), and preoperative intraocular pressure (P = 0.027) were correlated with higher postoperative tilt. Fifty eyes that underwent FLACS demonstrated mean postoperative decentration of 0.21 ± 0.13 mm and tilt of 4.64 ± 1.48°. Compared with the conventional surgery group, the FLACS group significantly differed in postoperative decentration (0.30 ± 0.12 mm, P < 0.001) but not in tilt (5.03 ± 1.35°, P = 0.173). Postoperative visual acuity did not significantly differ between the two groups. Conclusion: Patients who underwent FLACS demonstrated better IOL decentration and tilt than those who underwent conventional cataract surgery one-month post-surgery. However, differences in IOL decentration and tilt did not affect postoperative visual acuity.